Northern Bobwhite Brood Habitat Selection in South Florida - Nevena Martin; James A. Martin; John P. Carroll (National Quail Symposium Proceedings, 2017)
During the past 3 decades, Northern Bobwhite (Colinus virginianus; hereafter, bobwhite(s)) populations have decreased throughout most of their distribution. A variety of factors have been attributed as the cause for this decline including changes in land use, agricultural intensification, increased predation, and high chick mortality. We assessed fourth-order habitat selection of broods in south Florida to develop predictions of management strategies that favor bobwhite brood success. We analyzed canopy coverage at actual brood locations versus both random-within MCP home range locations and random-outside MCP home range locations. Average home range size was 5.53 ± 2.43 ha. Our data suggests that no single vegetation type can be used to predict use by bobwhite broods. The models we evaluated using Akaike’s Information Criterion (AIC) supports this belief. We also observed sod-forming grasses and forbs as the most prevalent vegetation types at brood and random-within MCP home range locations. Broad-leaved woody vegetation and legumes were more prevalent at brood locations than random locations. Our research demonstrates that plant community diversity is likely more important than a single functional group of plants. We believe that, at the ranch level, a combination of vegetation management within pastures, as well as large-scale management increasing interspersion of desirable vegetation communities will provide bobwhites quality habitat during all periods of their life cycle.
Keywords: brood; Colinus virginianus; Florida; habitat selection; northern bobwhite; quail